Establishing biotinidase reference interval, a foundation stone for newborn screening of biotinidase deficiency in Pakistan - Bibi, Afshan; Zujaja Hina Haroon; Amna Shujaat; Muhammad Aamir; Sobia Irum; Syed Raza Jaffar (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the reference interval of biotinidase activity in healthy neonates. Method: The cross-sectional study was conducted at the Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology, Rawalpindi, Pakistan, from May to November 2019, and comprised blood samples collected from healthy neonates aged 2-6 days. The samples were collected on filter paper and analysed on genetic screening processor based on dissociation-enhanced lanthanide flouroimmunoassay. Data was analysed using SPSS 21. Results: Of the 120 dried blood spot specimens, 81(67.5%) were from male babies and 39(32.5%) from female babies. Reference interval for biotinidase activity, based on 2.5th and 97.5th percentiles, was from 3.0 to 11.0 nmol/ml/min. Conclusion: Screening of newborns for biotinidase deficiency is crucial to prevent irreversible neurological damage. Key Words: Biotinidase reference interval, Biotinidase deficiency, Newborn screening in Pakistan.